A Companion to translation studies - Bermann, Sandra 1947-; Porter, Catherine 1941- (Wiley Blackwell, 2014)
"This companion offers a wide-ranging introduction to the rapidly expanding field of translation studies, bringing together some of the best recent scholarship to present its most important current themes Features new work from well-known scholars Includes a broad range of geo-linguistic and theoretical perspectives Offers an up-to-date overview of an expanding field A thorough introduction to translation studies for both undergraduates and graduates Multi-disciplinary relevance for students with diverse career goals"--Publisher.